A modified dinucleotide for site-specific RNA-labelling by transcription priming and click chemistry - Samanta, Ayan; Krause, André; Jäschke, Andres (Chemical communications, 2014)
An improved strategy for RNA labelling using an alkyne-carrying dinucleotide is reported. This involves near-quantitative priming by phage RNA-polymerases followed by conjugation of different labels using click chemistry. Moreover, these transcripts bear a ligation compatible 5′-end, and thus through ligation the terminal label can be transformed to an internal one.
First published 17 Oct 2013
Gesehen am 09.10.2020